Characterization of Alkaline Treatment and Fiber Content on the Physical, Thermal, and Mechanical Properties of Ground Coffee Waste/Oxobiodegradable HDPE Biocomposites. (27th August 2017) - Tan, Ming Yee; Nicholas Kuan, Hoo Tien; Lee, Meng Chuen
Abstract : Effect of alkali treatment on ground coffee waste/oxobiodegradable HDPE (GCW/oxo-HDPE) composites was evaluated using 5%, 10%, 15%, and 20% volume fraction of GCW. The composites were characterized using structural (Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM)), thermal (thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC)), mechanical (tensile and impact test) properties, and water absorption. FTIR spectrum indicated the eradication of lipids, hemicellulose, lignin, and impurities after the treatments lead to an improvement of the filler/matrix interface adhesion. This is confirmed by SEM results. Degree of crystallinity index was increased by 5% after the treatment. Thermal stability for both untreated and treated GCW composites was alike. Optimum tensile result was achieved when using 10% volume fraction with enhancement of 25% for tensile strength and 24% for tensile modulus compared to untreated composite. Specific tensile strength and modulus had improved as the composite has lower density. The highest impact properties were achieved when using 15% volume fraction that lead to an improvement of 6%. Treated GCW composites show better water resistance with 57% improvement compared to the untreated ones. This lightweight and ecofriendly biocomposite has the potential in packaging, internal automotive parts, lightweight furniture, and other composite engineering applications.